Some exact solutions to the generalized Korteweg–de Vries equation and the system of shallow water wave equations - Dolapci, Ihsan Timuçin Timuçin; Yıldırım, Ahmet (Nonlinear Analysis: Modelling and Control, 2013)
In this paper, we establish exact solutions for nonlinear evolution equations in mathematical physics. The exp-transform method is proposed to seek solitary solutions, periodic solutions and compaction-like solutions of nonlinear differential equations. The generalized KdV equation and the system of the shallow water wave equation are chosen to illustrate the effectiveness and convenience of the method.